Clinical Utility of Next-Generation Sequencing-Based Molecular Panel in Thyroid Nodules - Hetashvi Gondaliya; Suruchi Aggarwal; Kranti Khadilkar; Shivaprasad S. Kumbenahalli; Basavaraj Sooragonda; Anirudh J. Shetty; Vijay Pillai; Vidhya Bhushan; Vivek Shetty; Yogesh Dokhe; Akhila Lakshmikantha; Subramanian Kannan (Indian Journal of Endocrinology and Metabolism)
Introduction: The molecular testing of indeterminate thyroid nodules (ITNs) empowers clinicians to make informed treatment decisions. Despite being recommended by the ATA 2015 guidelines, the utility of molecular testing in India is hindered by challenges related to availability and cost-effectiveness, thereby limiting its widespread adoption. We aimed to evaluate the clinical utility of next-generation sequencing (NGS)-based molecular testing in Indian patients with ITNs. Methods: The study included patients with Bethesda III and IV and selected Bethesda II nodules who underwent Thyrotrack NGS-based assay on fine needle aspirate (FNA) material. Surgery was recommended for patients with clinically significant mutations, while others were followed sonographically. Post-surgical histopathology results were compared with mutation variants to calculate the sensitivity, specificity, and negative predictive value of the NGS assay. Results: Among 35 patients (mean age 37.7 ± 12.4 years, 80% female), 20 (57%) had clinically significant mutations. Surgery was performed on 11 patients. The most common mutation was RAS (detected in 15 patients), followed by BRAF, TSH-R, ETV6/NTRK3, and PAX8/PPARG. Post-surgical outcomes showed an overall sensitivity of 86% and a specificity of 74%, with a negative predictive value of 94%. Among the mutation-negative group, only one patient had a malignancy, and the rest were benign showing a high negative predictive value of the NGS-based testing. Conclusion: NGS-based assays provide a reliable and cost-effective option for ruling out malignancy in ITNs in India, offering a high negative predictive value and complementing ACR-TIRADS and Bethesda cytology classifications.